PELAKSANAAN JUAL BELI MOBIL BEKAS DI SHOWROOM SKY MOTOR PEKANBARU - Jessica Olivia; Hayatul Ismi; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The need for private transportation in the midst of a pandemic that has notended, has an impact on used car sales which are slowly but surely rising again.This used car buying and selling activity will of course begin with an agreementbetween the two parties that is included in the contents of the agreement. Usuallythe form of an oral agreement or written agreement signed on stamp duty by bothparties. In a broad sense, an agreement means any agreement that is caused as alegal consequence as agreed by the parties. In connection with the buying andselling of used cars, problems often occur that do not only originate from businessactors, but also from buyers who are interested in a used car in a showroom, oneof which the author has built in the following research.This type of research can be classified in the type of descriptive qualitativeresearch, because in this study the author directly conducts research on thelocation or place under study in order to provide a complete picture and explainthe problem under study. This research was conducted at the Sky MotorShowroom Pekanbaru, while the population and sample were all parties relatedto the problems studied in this study, the data sources used were primary data,primary data, secondary data and tertiary data. Data collection techniques in thisstudy by observation, interviews and literature study.The results of this study are the car buyer has defaulted, the sale andpurchase agreement becomes invalid because the car buyer does not pay thedown payment as agreed in the agreement. According to the provisions of Article1243 of the Civil Code, compensation due to non-fulfillment of a new obligationthat is required if the debtor after being declared negligent in fulfilling hisengagement continues to neglect it, or something that must be given or done canonly be given or done within the time period that has passed. The loss wasdeclared obliged to be replaced by the debtor starting from the time he wasnegligent on January 20, 2022 which should have been repaid on January 19,2022. Finally, payment of the remaining money and fines for late payment ofadvances by the buyer in stages with the completion of the payment of fines onMarch 2, 2022.Keywords : Agreements – Sell and Buy – Used Cars – Rights and Obligations